"Our Victims Define Our Borders": Commemorating Yugoslav Partisans in the Italo-Yugoslav Borderland. (May 2017) - Klabjan, Borut
This article is part of the special section titled From the Iron Curtain to the Schengen Area, guest edited by Wolfgang Mueller and Libora Oates-Indruchová. This article discusses local cultures of remembrance of Yugoslav partisans fallen during World War II in Trieste, now part of Italy, and investigates the role of memory activists in managing vernacular memory over time. The author analyses the interplay between memory and the production of space, something which has been neglected in other studies of memory formation. On the basis of local newspaper articles, archival material, and oral interviews, the essay examines the ideological imprint on the local cultural landscape, contributing to a more complex understanding of memory engagement. The focus is on grassroots initiatives rather than state-sponsored heritage projects. This article argues that memory initiatives are not solely the outcome of national narratives and top–down ideological impositions. It shows that official narratives have to negotiate with vernacular forms of memory engagement in the production of a local mnemonic landscape.